Perceptions of the Use of EveryCircuit-Based Virtual Laboratory on Dynamic Electricity Material - Hajar, Siti; Akbar, Muhammad; Silaban, Adeline; G. D Lasmono S., Paulus (Universitas Muhammadiyah Makassar, 2024)
The integration of virtual laboratories has become an innovative solution for enhancing physics education, particularly in addressing challenges related to limited access to physical laboratory resources. This study aims to investigate the perceptions of physics education students at Cenderawasih University regarding the use of EveryCircuit-based virtual laboratories in learning dynamic electricity concepts. A quantitative descriptive approach was employed, with data collected through an online questionnaire distributed to 16 students. The questionnaire assessed three key aspects: material comprehension, usability of the EveryCircuit application, and students’ motivation and skills. The results revealed that 42.50% of students agreed that the EveryCircuit-based virtual laboratory improved their understanding of dynamic electricity concepts, while 46.87% agreed on its usability, and 43.75% reported enhanced motivation and skills. Despite positive responses, some challenges emerged, including limited proficiency in using EveryCircuit and occasional technical barriers such as unstable internet connections. Overall, the findings suggest that EveryCircuit-based virtual laboratories offer an effective alternative for teaching dynamic electricity, promoting a more interactive and accessible learning environment. The study recommends further research to address technical challenges and improve training on the use of virtual laboratory tools. Additionally, incorporating complementary digital resources and hands-on guidance could enhance the overall effectiveness of virtual laboratory implementation in physics education.